Integrated Management System: the implantation of a partnership in town of São José dos Campos - Inajara Iana Silva; Denise Pinheiro (Universidade Estadual Paulista Júlio de Mesquita Filho, 2009)
The paper intends to describe and analyze the implementation of the partnership that was signed between the Municipal Secretariat of Education of São Jose dos Campos and Embraer Institute of Education and Research, under consultancy of Pitágoras Foundation with the goal to install a model of corporate management in network of municipal education. Thus, it was used data on enrollment, official documents and interviews conducted in 2008 with representatives of the Embraer Institute, Pitágoras Foundation and the Municipal Department of Education. The article shows that adherence to the corporate management model named Integrated Management System (SGI) wasn´t the need, but the offer of the Embraer. Also we note that the partnership can´t guarantee the promised public education of "quality", in mind as organizes the educational business system as the SGI, may influence the responsibility of schools to develop and implement its pedagogical proposal, damaging school´s pedagogical autonomy.